Hepatic steatosis in participants in a program of low-dose CT screening for lung cancer. Issue 94 (September 2017) - Chen, Xiangmeng; Li, Kunwei; Yip, Rowena; Perumalswami, Ponni; Branch, Andrea D.; Lewis, Sara; Del Bello, David; Becker, Betsy J.; Yankelevitz, David F.; Henschke, Claudia I.
Highlights: Non-contrast low-dose CT of the chest can detect HS in asymptomatic participants. Male, diabetes, high BMI, and emphysema were significant predictors of HS. Aspartate aminotransferase and alanine aminotransferase were significantly negatively correlated with liver attenuation. Recommend further evaluation if liver attenuation <40 HU and/or L/S ratio <0.8. Abstract: Objective: Determine the frequency of moderate-to-severe hepatic steatosis (HS) in asymptomatic participants in a low-dose CT (LDCT) screening program for lung cancer, to identify risk factors, and develop recommendations. Methods: Baseline LDCT scans of the chest of 170 participants in an IRB-approved study between August 2011 and April 2016 were reviewed. Demographic variables, comorbidities, and liver function tests were documented. Hepatic and splenic attenuation values hounsfield unit (HU) were measured. Regression analyses were performed. Results: Average liver attenuation was 57.6 HU (standard deviation (SD) 9.3) and average liver/spleen (L/S) ratio was 1.3 (SD 0.3). Liver attenuation was <40 HU for 9 (5.3%), liver/spleen (L/S) ratio <0.8 for 6 (3.5%), and either <40 HU or L/S ratio <0.8 for 9 (5.3%). Male sex (p = 0.004), diabetes (p = 0.0005), emphysema (p = 0.03), and high BMI (p = 0.0006) were significant predictors of HS. Aspartate aminotransferase (p = 0.0018) and alanine aminotransferase (p = 0.012) were negatively correlated with liver attenuation. Reduced serum levels of alpha-1-antitrypsin may be a common factor of emphysema and HS. Conclusion: LDCT can detect HS in asymptomatic participants with frequencies similar to previous reports. If liver attenuation is below 40 HU and/or L/S ratio below 0.8, further evaluation of HS to the primary care physician or liver specialist is recommended.